The influence of organizational culture, principal leadership, and teacher work motivation on teacher performance - Indra Hasan; Happy Fitria; Achmad Wahidy (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This research aims to describe the influence of organizational culture, principal leadership, and teacher work motivation on teacher performance in SMAN 1 Air Sugihan. The method used is a quantitative research method with a population as well as a sample of 33 people. The data collection techniques used were questionnaires and observations. The data analysis used descriptive analysis, simple regression, and multiple regression with the help of the IBM SPSS version 25,0 Program. The results showed that; (1) there is a positive and significant influence between organizational culture on teacher performance, (2) there is a positive and significant influence between principal leadership on teacher performance, (3) there is an influence which is positive and significant between teacher work motivation on teacher performance, and (4) there is a positive and significant influence between organizational culture, principal leadership, and teacher work motivation on teacher performance.